Efecto de la inclusión de azolla spp. en la alimentación de pollos de engorde sobre los parámetros productivos. - Sanjines Yunga, Yustin Gerardo (Machala : Universidad Técnica de Machala, 2022)
The present investigative work was carried out in the "Santa Inés" farm located in the Faculty of Agricultural Sciences of the Technical University of Machala, Province of El Oro. The proposed objective was to demonstrate the effect of feeding with the inclusion of different percentages of azolla in productive parameters of Cobb 500 line broilers. A completely randomized experimental design was applied for 7 weeks in which 160 broilers (Cobb 500 line) were used, divided into 4 experimental groups, with 4 replicates and 10 replicates. birds in each one, distributed in cages with an approximate diameter of 0.80 m at the beginning of the experiment and then enlarged to 1 m in diameter, under the management and biosafety regulations that govern a poultry farm; Depending on the area and location of the shed, a basic vaccination plan was carried out that consisted of the single application of the Gumboro vaccine (Gumbo-Vac) on the fifth day and New Castle (New+Bron) on the seventh day, both ocular routes. The feeding was divided into 2 stages, the first of 3 weeks with the initial balanced feed from the BioAlimentar commercial house and the second stage of 3 weeks with the balanced commercial fattening Pro Aves from Pronaca, with a week of transition between both stages; In addition, the incorporation of Azolla spp. from the third day, in 4 treatments, the first treatment (T1 or control) was composed only of commercial balanced, in the second treatment (T2) 5% of Azolla spp. was incorporated, that replaced this same percentage of balanced, in the third treatment (T3) 10% of Azolla spp. was incorporated, instead of the commercial balanced and in the fourth treatment (T4) 15% of Azolla spp. was incorporated, instead of balanced . For the calculation of food to be consumed by the birds, a consumption table from the Cobb 500 Manual was taken as a reference. The productive parameters taken as variables were: weekly live weight (g), weight gain (g), feed consumption (g) and feed conversion ratio. For the statistical analysis of employment in the IBM SPSS version 25 program, in which an analysis of variance was performed for a single factor (Anova) and Duncan's test to compare the means of the treatments and determine significant differences with a reliability interval of 95%. The results obtained show that, at the end of the experiment, there are no significant differences between the live weights, but arithmetically the control treatment (T1) obtained the highest weight (3864.98 g), followed by the second treatment (3853.85 g), third treatment (3817.13 g) and fourth treatment (3682.26 g); In terms of weight gain, the control treatment together with the second treatment were significantly higher than treatment three and even more than treatment four. Regarding food consumption, the fourth treatment (T4) with the inclusion of 15% of Azolla spp., reaches the highest consumption (72539.25 g) followed by the second treatment (70441.5 g), third treatment (70132, 25 g) and control treatment (68755.75 g); Similarly, the best total feed conversion ratio is achieved with the control treatment (T1) reaching a value of 1.78, followed by the second treatment (1.83), the third treatment (1.94) and the fourth treatment. (2.08). Therefore, it was concluded that Azolla spp., can replace up to 5% of the commercial feed in broiler chickens without affecting the production parameters that are normally obtained when rearing with feed based on commercial feed.
El presente trabajo investigativo se llevó a cabo en la granja “Santa Inés” ubicada en la Facultad de Ciencias Agropecuarias de la Universidad Técnica de Machala, Provincia de El Oro. El objetivo propuesto fue demostrar el efecto de la alimentación con inclusión de diferentes porcentajes de azolla en parámetros productivos de pollos de engorde línea Cobb 500. Se aplicó un diseño experimental completamente al azar, durante 7 semanas en el que se emplearon 160 pollos de engorde (línea Cobb 500), divididos en 4 grupos experimentales, con 4 réplicas y 10 aves en cada una, distribuidos en jaulas con un diámetro aproximado de 0,80 m al inicio del experimento y luego se agrandaron a 1 m de diámetro, bajo el manejo y las normas de bioseguridad que rigen un plantel avícola; según la zona y ubicación del galpón se ejecutó un plan vacunal básico que consistió en la única aplicación de vacuna Gumboro (Gumbo-Vac) en el quinto día y New Castle (New+Bron) al séptimo día, ambas vía ocular. La alimentación se dividió en 2 etapas, la primera de 3 semanas con el balanceado inicial de la casa comercial BioAlimentar y la segunda etapa de 3 semanas con balanceado engorde comercial Pro Aves de Pronaca, con una semana de transición entre ambas etapas; además, de la incorporación a partir del tercer día de Azolla spp., en 4 tratamientos, el primer tratamiento (T1 o testigo) estuvo compuesto únicamente de balanceado comercial, en el segundo tratamiento (T2) se incorporó 5% de Azolla spp., que sustituyó este mismo porcentaje de balanceado, en el tercer tratamiento (T3) se incorporó un 10% de Azolla spp, en lugar del balanceado comercial y en el cuarto tratamiento (T4) se incorporó 15% de Azolla spp., en lugar de balanceado. Para el cálculo de alimento a consumir por parte de las aves se tomó como referencia una tabla de consumos del Manual Cobb 500. Los parámetros productivos tomados como variables fueron: peso vivo semanal (g), ganancia de peso (g), consumo de alimento (g) e índice de conversión alimenticia. Para el análisis estadístico de empleo en programa IBM SPSS versión 25 en el que se realizó un análisis de varianza para un solo factor (Anova) y el test de Duncan para comparar las medias de los tratamientos y determinar diferencias significativas con un intervalo de confiabilidad del 95%. Los resultados obtenidos muestran que, al final del experimento no existe diferencias significativas entre los pesos vivos, pero aritméticamente el tratamiento testigo (T1) obtuvo el mayor peso (3864,98 g), seguido por el segundo tratamiento (3853,85 g), tercer tratamiento (3817,13 g) y el cuarto tratamiento (3682,26 g); en cuanto a la ganancia de peso, el tratamiento testigo en conjunto con el segundo tratamiento fueron significativamente mayores al tratamiento tres y aun mas al tratamiento cuatro. Respecto al consumo de alimento, el cuarto tratamiento (T4) con la inclusión del 15% de Azolla spp., alcanza el mayor consumo (72539,25 g) seguido por el segundo tratamiento (70441,5 g), tercer tratamiento (70132,25 g) y tratamiento testigo (68755,75 g); de igual manera el mejor índice de conversión alimenticia total se logra con el tratamiento testigo (T1) alcanzando un valor de 1,78, seguido por el segundo tratamiento (1,83), el tercer tratamiento (1,94) y el cuarto tratamiento (2,08). Por lo que se concluyó que la Azolla spp., puede reemplazar hasta un 5% el balanceado comercial en la alimentación de pollos de engorde sin afectar los parámetros productivos que normalmente se obtienen al realizar una crianza con una alimentación a base de balanceado comercial.
Keywords: PESO VIVO; GANANCIA DE PESO; CONSUMO DE ALIMENTO; INDICE DE CONVERSION